2018
DOI: 10.1111/bjhp.12333
|View full text |Cite
|
Sign up to set email alerts
|

Shaping parents, shaping penises: How medical teams frame parents’ decisions in response to hypospadias

Abstract: The best interests of children with hypospadias may well be served when psychological pathways are highlighted, providing opportunities to support the flourishing of children whose genital appearance raises the question of medical intervention. Statement of Contribution What is already known on this subject? Framing significantly affects medical decision-making in ways that people typically fail to perceive. Parents frequently consent to non-essential hypospadias (penile) surgery for their sons, despite the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…First, this study is one of very few to respond to Liao & Simmonds’ () call for studies of public understanding of intersex, and it extends findings that medical and psychosocial frames affect the perceived harms and benefits of medical intervention on intersex traits (Roen & Hegarty, ; Streuli et al, ). Within a medical framing, medical harms may make sense as a “necessary evil” that seem to co‐occur with interventions aimed at concealing or minimizing intersex traits.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…First, this study is one of very few to respond to Liao & Simmonds’ () call for studies of public understanding of intersex, and it extends findings that medical and psychosocial frames affect the perceived harms and benefits of medical intervention on intersex traits (Roen & Hegarty, ; Streuli et al, ). Within a medical framing, medical harms may make sense as a “necessary evil” that seem to co‐occur with interventions aimed at concealing or minimizing intersex traits.…”
Section: Discussionsupporting
confidence: 53%
“…Stigma reduction in this area might require unlearning these taken‐for‐granted assumptions about gender categories (Garfinkel, ). In practice, DSD clinicians often continue to frame health and well‐being for parents who find themselves challenged by decisions about medical interventions in ways that reproduce those gender binary beliefs (Roen et al, ; Roen & Hegarty, ). Incorporating greater awareness about non‐binary genders into medical education for clinicians who work in this area may address clinicians’ gender binary beliefs and judgments about the necessity for medical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In male newborns with severe hypospadias, urological surgery is certainly indicated for functional repair (80). Although a recent review (81) found that 80% of men are satisfied with childhood hypospadias repair, it is advisable to refrain from invasive surgery that is not essential for health and to encourage patient participation and decisions in the choices regarding the sexual sphere (82).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…57 More critical approaches highlight that the effect of framing is often underestimated by medical professionals and that, in favour of their child, nonmedical pathways can also be opened up for parents who have sons with hypospadias. 58 The issue of hypospadias illustrates the problem of knowledge gaps that is so relevant in the more "classical" dsd conditions, such as CAIS, too.…”
Section: Issues Associated With the Most Difficulty And Uncertainty Imentioning
confidence: 99%